2015
DOI: 10.1016/j.heares.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear neuropathy in human presbycusis: Confocal analysis of hidden hearing loss in post-mortem tissue

Abstract: Recent animal work has suggested that cochlear synapses are more vulnerable than hair cells in both noise-induced and age-related hearing loss. This synaptopathy is invisible in conventional histopathological analysis, because cochlear nerve cell bodies in the spiral ganglion survive for years, and synaptic analysis requires special immunostaining or serial-section electron microscopy. Here, we show that the same quadruple-immunostaining protocols that allow synaptic counts, hair cell counts, neuronal counts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
271
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(296 citation statements)
references
References 49 publications
23
271
0
2
Order By: Relevance
“…The patients' audiograms (figure 2I) with high frequency hearing loss resemble those of sensory presbycusis, caused by degeneration of the distal-most segments of the auditory neurons or their synaptic contacts 30. Not much is known about VLCFA requirements for inner ear development and function.…”
Section: Discussionmentioning
confidence: 99%
“…The patients' audiograms (figure 2I) with high frequency hearing loss resemble those of sensory presbycusis, caused by degeneration of the distal-most segments of the auditory neurons or their synaptic contacts 30. Not much is known about VLCFA requirements for inner ear development and function.…”
Section: Discussionmentioning
confidence: 99%
“…In noiseexposed humans and animals, acoustic trauma (noise-induced hearing loss) leads to hair cell damage and causes a threshold shift [19,20]. Recent studies have indicated that ageing and/or moderate noise exposure can result in hidden hearing loss [21][22][23], which causes difficulties in speech discrimination and temporal processing in a noisy environment [24]. It can be detected physiologically, and is characterized by reduced amplitude in the sound-evoked spiral ganglion neuron activity (the first peak of the ABR waveform) [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…2 ). In humans, the absolute latencies and supra-threshold amplitudes of waves, ABR wave I (distal peripheral portion of the AN [90] ), ABR wave III (fibers from cochlear nucleus to caudal auditory pons and superior olivary complex [91] ), ABR wave VI (medial geniculate body or the auditory thalamus), or ARB wave V (believed to correspond with the IC in the midbrain [92,93] ) can be analyzed for various stimulus intensity levels and, for example, recording time of ABR measurements that should be set at >10 ms. An increasing body of evidence demonstrates that, due to altered leisure behavior and demographic crisis, the hidden hearing loss and auditory neuropathy are likely widely prevalent over time [94][95][96] , contributing to presbycusis [62,64,97] or hyperacusis and tinnitus [21,22,98] .…”
Section: Functional Biomarker For An Fiber Responses: Abr Wave Fine Smentioning
confidence: 99%